The Effect of Mechanical State on the Equilibrium Potential of Alkali Metal/Ceramic Single‐Ion Conductor Systems. Issue 29 (16th June 2021) - Carmona, Eric A.; Wang, Michael J.; Song, Yueming; Sakamoto, Jeff; Albertus, Paul
Abstract: The relationship between mechanical stress states and interfacial electrochemical thermodynamics of Li metal/Li6.5 La3 Zr1.5 Ta0.5 O12 and Na metal/Na‐β"‐Al2 O3 systems are examined in two experimental configurations with an applied uniaxial load; the solid electrolytes are pellets and the metal electrodes high‐aspect‐ratio electrodes. The experimental results demonstrate that 1) the change in equilibrium potential at the metal/electrolyte interface, when stress is applied to the metal electrode, is linearly proportional to the molar volume of the metal electrode, and 2) the mechanical stress in the electrolyte has a negligible effect on the equilibrium potential for an experimental setup in which the electrolyte is stressed and the electrode is left unstressed. Solid mechanics modeling of a metal electrode on a solid electrolyte pellet indicates that pressure and normal stress are within ≈0.5 MPa of each other for the high aspect ratio (≈1:100 thickness:diameter in our study) Li metal electrodes under loads that exceed yield conditions. This work should aid in advancing the quantitative understanding of alkali metal dendrite formation within incipient cracks and their subsequent growth, and pore formation upon stripping, both situations where properly accounting for the impact of mechanical state on the equilibrium potential is of critical importance for calculating the current distribution. Abstract : The first careful measurements of how applied stresses alter the thermodynamic state of alkali metal electrode/single‐ion conducting electrolyte systems are conducted. Applied stress on the metal electrode causes a change in equilibrium potential that is linearly proportional to the molar volume of the metal electrode, and the mechanical stress on the electrolyte has a negligible effect on the equilibrium potential.